2000
DOI: 10.1017/s1357729800055132
|View full text |Cite
|
Sign up to set email alerts
|

Effect of offering maize, linseed or tuna oils throughout pregnancy and lactation on sow and piglet tissue composition and piglet performance

Abstract: The effects of different dietary essential fatty acids on piglet tissue composition at birth and performance until 7 days post weaning were investigated by offering the sow diets containing (17·5 g oil per kg diet) either maize oil (MO) as a control treatment, tuna oil (TO) as a source of long chain n-3 polyunsaturated fatty acids, particularly 22:6 n-3, or a mixture of maize and linseed oils (LO) which supplied the same amount of n-3 acids as TO but in the form of 18:3 n-3. Ten sows were allocated to each tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

20
56
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(77 citation statements)
references
References 30 publications
20
56
1
Order By: Relevance
“…BW from birth until the end of the nursery period (34 days after weaning) tended to be higher in litters from n-3 LCPUFA fed sows in the present study, again consistent with earlier studies (Rooke et al, 2000 and2001b;Mateo et al, 2009). As Taugbol et al (1993 and Fritsche et al (1993) did not find an effect on weaning weight when n-3 LCPUFA supplementation started at day 107 of gestation, and Smits et al (2011) did not find an effect on piglet growth and weaning weight when feeding n-3 LCPUFAs from 8 days before farrowing, longer periods of supplementation may be needed in gestation to produce positive effects on litter weaning weight.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…BW from birth until the end of the nursery period (34 days after weaning) tended to be higher in litters from n-3 LCPUFA fed sows in the present study, again consistent with earlier studies (Rooke et al, 2000 and2001b;Mateo et al, 2009). As Taugbol et al (1993 and Fritsche et al (1993) did not find an effect on weaning weight when n-3 LCPUFA supplementation started at day 107 of gestation, and Smits et al (2011) did not find an effect on piglet growth and weaning weight when feeding n-3 LCPUFAs from 8 days before farrowing, longer periods of supplementation may be needed in gestation to produce positive effects on litter weaning weight.…”
Section: Discussionsupporting
confidence: 93%
“…Evidence that n-3 LCPUFAs in the sow's diet are taken up into the blood stream (Fritsche et al, 1993;Rooke et al, 2000;Brazle et al, 2009) was confirmed by a 10-fold increase in serum EPA and DHA of n-3 LCPUFA supplemented sows in the present study, and as also reported by Rooke et al (2000), was associated with a decrease in serum LCPUFA 5 long-chain polyunsaturated fatty acids; CL 5 corpora lutea; CON 5 control; r.s.d. 5 residual standard deviation; SFA 5 saturated fatty acids; MUFA 5 mono-unsaturated fatty acids; nd 5 non-detectable.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations